On the Use of Deep Reinforcement Learning for Visual Tracking: A Survey - Giorgio Cruciata; Liliana Lo Presti; Marco La Cascia (IEEE Access, 2021)
This paper aims at highlighting cutting-edge research results in the field of visual tracking by deep reinforcement learning. Deep reinforcement learning (DRL) is an emerging area combining recent progress in deep and reinforcement learning. It is showing interesting results in the computer vision field and, recently, it has been applied to the visual tracking problem yielding to the rapid development of novel tracking strategies. After providing an introduction to reinforcement learning, this paper compares recent visual tracking approaches based on deep reinforcement learning. Analysis of the state-of-the-art suggests that reinforcement learning allows modeling varying parts of the tracking system including target bounding box regression, appearance model selection, and tracking hyper-parameter optimization. The DRL framework is elegant and intriguing, and most of the DRL-based trackers achieve state-of-the-art results.